Aladdin [videorecording (DVD)] - Clements, Ron; Musker, John (Walt Disney signature collection., 2019)
In the heat of an enchanted city, a commoner named Aladdin and his mischievous monkey Abu battle to save the free-spirited Princess Jasmine from the schemes of the evil sorcerer Jafar. Aladdin's whole life changes with one rub of a magic lamp as a fun-loving, shape-shifting Genie appears and grants him three wishes, setting him on an incredible journey of discovery.